PERLINDUNGAN HAK CIPTA TERHADAP NFT "GHOZALI EVERYDAY" DI INDONESIA: - Muhammad Syaroni Putra; Aline Gratika Nugrahani (Reformasi Hukum Trisakti, 2023)
The development of technology and science has provided significant changes in human life. The problems in this research are: (1) can NFT be a means to protect the copyrighted work "Ghozali Everyday" against copyright infringement?; and (2) what legal steps can Ghozali take when the work is made into NFT without permission based on Law Number 28 of 2014 concerning Copyright? This research is a normative type, descriptive analytical in nature, sourced from primary and secondary data, analyzed qualitatively, and drawn conclusions deductively. The conclusion is that NFT can be a means of protecting the copyrighted work "Ghozali Everyday" against copyright infringement, by turning the copyrighted work into an NFT and there are legal remedies that Ghozali can take if the work is made into NFT without permission, including efforts to report through a protection mechanism. provided by OpenSea based on the Blockchain system, and dispute resolution through alternative dispute resolution, Arbitration or Court by article 95 paragraph 1 of Law no. 28 of 2014 concerning Copyright.